Pengaruh Bauran Pemasaran Jasa (Process, Physiycal Evidence, People) Terhadap Keputusan Pembelian: (Survei pada Konsumen Sultan Laundry BRP Tasikmalaya) - Selvia Nurahmah Indriati (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of the service marketing mix (process, physical evidence, people) on purchasing decisions on consumers of Sultan Laundry BRP Tasikmalaya. The type of research used is a quantitative method with a survey approach. The population in this study are consumers of Sultan Laundry BRP Tasikmalaya. The sample is 100 people. The analytical tool used is multiple linear regression. The results of the study obtained multiple linear regression equations (Y=15,168+0,664X1+ 0,260X2+0,237X3). The results of the hypothesis simultaneously (F test) were obtained (Fcount value of 7.863> Ftable value of 2.70) which means that process, physical evidence, people have a significant effect on consumer purchasing decisions of Sultan Laundry BRP Tasikmalaya. Meanwhile, from the results of the partial hypothesis (t test) obtained for the X1 process variable (tcount 2,914 > ttable 1,985) then the process has a significant effect on purchasing decisions. For the variable X1 phsiycal evidence (tcount 2,311 > ttable 1,985) then the phsiycal evidence has a significant effect on purchasing decisions. For the variable X3 people (tcount 2.144 > ttable 1.985) then people have a significant effect on purchasing decisions. The Correlation Coefficient (R) of 0.444 means that it has a relationship between process, physical evidence, and people on consumer purchasing decisions of Sultan Laundry BRP Tasikmalaya. The coefficient of determination (R2) is 0.197 or 19%, meaning that purchasing decisions are influenced by the process (process) of physical evidence (physical evidence), people (people) by 19%. While the remaining 81% is influenced by other factors not examined. The magnitude of the influence of these other variables is often referred to as the € error.